Pemfigus Vulgaris - Wizar Putri Mellaratna; Cut Winda Agustia (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Pemphigus vulgaris (PV) is a chronic intraepidermal bullous disease that causes extensive skin lesions. Pemphigus vulgaris initially appears in the form of vesicles and loose-walled bullae that break easily on normal skin, which then develop into bullae with an erythematous base, then rupture, causing erosion, excoriation, which is usually accompanied by crusting and pain. Bullae occur due to damage or damage to intercellular adhesion due to IgG autoantibodies to desmoglein 3, causing epithelial cells called acantholysis (epidermal cell separation reaction). The hallmark of pemphigus is erosion that extends into normal skin by pulling on remnants of the blister wall or rubbing on the periphery of an active lesion. Erosion can be induced on normal-appearing skin away from the active lesion by mechanical stress or shear, a phenomenon known as the Nikolsky sign. Prognosis before corticosteroids are used, death occurs in 50% of patients within the first year. Treatment with corticosteroids makes the prognosis better. Pemphigus vulgaris in the early stages will be easier to control than those with widespread manifestations, the mortality rate will increase if there is a delay in therapy.